Lipoxygenase inhibitors induce arrest of tumor cells in S-phase of the cell cycle - Hofmanová, J; Soucek, K; Pacherník, J; Kovaríková, M; Hoferová, Z; Minksová, K; Netíková, J; Kozubík, A (Neoplasma, 2002)
Inhibitors of the lipoxygenase pathway of arachidonic acid metabolism represent a potential anti-tumor drugs. These compounds have been found to inhibit the growth and induce the apoptosis of various tumor cells both in vitro and in vivo. In this study, the effects of the lipoxygenase inhibitors esculetin and nordihydroguaiaretic acid (NDGA) on the progression of the cell cycle were investigated in eight mammalian cell lines of different origin. Flow cytometric analyses of cell cycle distribution after staining of DNA with propidium iodide or 7-aminoactinomycin D and DNA synthesis using incorporation of 5-bromo-2'-deoxy-uridine showed that both esculetin and NDGA suppress cell growth by interrupting the progression of cells through S-phase that results in their accumulation in this phase of the cell cycle. The possible mechanisms of these effects and the significance of the findings for the improvement of anticancer therapy targeted on cell cycle is discussed.
Keywords: S fáze; Cell Division; techniky in vitro; Humans; Bromodeoxyuridine; Tumor Cells, Cultured; Dose-Response Relationship, Drug; umbeliferony; lidé; Antioxidants; zvířata; myši; Arachidonic Acid; kyselina nordihydroguaiaretová; Umbelliferones; Mice; nádorové buňky kultivované; antioxidancia; bromodeoxyuridin; DNA Replication; inhibitory lipoxygenas; Lipoxygenase Inhibitors; Propidium; replikace DNA; propidium; In Vitro Techniques; vztah mezi dávkou a účinkem léčiva; S Phase; Animals; Masoprocol; DNA nádorová; kyselina arachidonová; DNA, Neoplasm; buněčné dělení